PENGARUH PENGHINDARAN PAJAK DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK - Yuliana, Nia; Furqon, Imahda Khoiri (Universitas Pembangunan Panca Budi, 2023)
The introduction of the self-assessment system has not been able to change taxpayers to carry out their tax activities independently and honestly. Tax planning is the first step in tax management. This step features an investigation and investigation of tax laws to align the selected type of tax savings with tax avoidance and tax evasion behavior in society. Tax avoidance is the right of all taxpayers, even so, taxpayers who do tax avoidance do not mean they can escape tax sanctions. Aggravating and fair sanctions against taxpayers who try to find loopholes or violate the law must be complied with.